Both sides of the saffron’s coin - Islam, Muhammad (International Journal of Medicine, 2017)
Saffron (Crocus sativus L.), a popular traditionally-used compound is known for its promising beneficial health effects. However, it has been reported to have a number of toxic effects in human and other animals. This paper aims to summarize saffronâ€™s beneficial and toxic effects. The findings suggest that sufficient precautions are needed in using saffron and its constituents as they have both beneficial and toxicological impacts on human.Â